Long‐term prognostic value of vasodilator stress cardiac magnetic resonance in patients with atrial fibrillation. (6th December 2021) - Weiss, Karl J.; Nasser, Sarah B.; Bigvava, Tamar; Doltra, Adelina; Schnackenburg, Bernhard; Berger, Alexander; Anker, Markus S.; Stehning, Christian; Doeblin, Patrick; Abdelmeguid, Mohamed; Talat, Mohamed; Gebker, Rolf; et al.
Abstract: Aims: Although the prevalence of coronary artery disease (CAD) is high among patients with atrial fibrillation (AF), studies on stress perfusion cardiac magnetic resonance (CMR) imaging frequently exclude patients with AF, and its prognostic and diagnostic value in high‐risk patients with suspected or known CAD remains unclear. Methods and results: In this longitudinal cohort study, we included 164 consecutive patients with AF during vasodilator perfusion CMR. Diagnostic value was evaluated regarding invasive coronary angiography in a subset of patients. We targeted a follow‐up of >5 years and used CMR results as stratification, and the primary outcome was major adverse cardiac events [MACE, cardiovascular (CV) death and myocardial infarction (MI)]. Secondary outcomes included late coronary revascularization or stroke and the components of the primary outcome. Of the whole cohort (73.8% male, mean age 72.2 years ± 7.8 SD), 99.4% were successfully scanned (163/164 patients). Median CHA2DS2‐VASc score was 4 [interquartile range (IQR) 3–5], and median 10‐year risk for CV events based on SMART risk score was high (24%, IQR 16–32%). Thirty‐two patients (19.6%) presented with ischaemia and 52 patients (31.9%) with late gadolinium enhancement (LGE). A combination of LGE and inducible ischaemia was present in 20 patients (12.3%). Diagnostic accuracy was 86.2% [confidence interval (CI) 68.3–96.1%]. The median follow‐up was 6.6 years (IQR 3.6–7.8). Ischaemia in vasodilator perfusion CMR was significantly associated with the occurrence of MACE [ P  < 0.01; hazard ratio (HR) 2.65, CI 1.39–5.08], as well as LGE ( P  = 0.03; 1.74, CI 1.07–3.64) and the combination of both ( P  < 0.01; HR 2.67, CI 1.59–5.62). After adjustment by age, left ventricular ejection fraction, and the presence of diabetes, ischaemia in vasodilator perfusion CMR remained significantly associated with the occurrence of MACE (2.10, CI 1.08–4.10; P  = 0.03). In secondary endpoint analysis, there was a significant association of ischaemia in CMR with CV death ( P  < 0.05; HR 1.93, CI 0.95–3.9) and MI ( P  < 0.01; HR 13, CI 1.35–125.4), while no significant association was found regarding the occurrence of revascularization ( P  = 0.45; HR 1.43, CI 0.57–3.58) or stroke ( P  = 0.99; HR 0.99, CI 0.21–2.59). Conclusions: Vasodilator stress perfusion CMR demonstrated an excellent diagnostic and significant prognostic value at long‐term follow‐up in high‐risk patients with persistent AF and suspected or known CAD.